Iron Biochemistry is Correlated with Amyloid Plaque Morphology in an Established Mouse Model of Alzheimer's Disease. - Telling, Neil; Everett, James; Collingwood, Joanna F.; Dobson, Jon; van der Laan, Gerrit; Gallagher, Joseph J.; Wang, Jian; Hitchcock, Adam P. (Cell Chemical Biology, 2017)
A signature characteristic of Alzheimer's disease (AD) is aggregation of amyloid-beta (Aß) fibrils in the brain. Nevertheless, the links between Aß and AD pathology remain incompletely understood. It has been proposed that neurotoxicity arising from aggregation of the Aß1-42 peptide can in part be explained by metal ion binding interactions. Using advanced X-ray microscopy techniques at sub-micron resolution, we investigated relationships between iron biochemistry and AD pathology in intact cortex from an established mouse model over-producing Aß. We found a direct correlation of amyloid plaque morphology with iron, and evidence for the formation of an iron-amyloid complex. We also show that iron biomineral deposits in the cortical tissue contain the mineral magnetite, and provide evidence that Aß-induced chemical reduction of iron could occur in vivo. Our observations point to the specific role of iron in amyloid deposition and AD pathology, and may impact development of iron-modifying therapeutics for AD.
This is the final published version of the article (version of record). It first appeared online via Elsevier at http://dx.doi.org/10.1016/j.chembiol.2017.07.014 - please refer to any applicable terms of use of the publisher.
Keywords: RC Internal medicine; Alzheimer's disease; amyloid-beta; redox-active iron; ferrous iron; magnetite; X-ray spectromicroscopy; scanning transmission X-ray microscopy; STXM; x-ray magnetic circular dichroism; diffuse plaque